Paul Maenz Köln Ausstellungs-Saison 1984/85. - Paul Maenz, Köln (Köln : Galerie Paul Maenz, 1985)
Dokoupil, Jiri Georg ; Fetting, Rainer ; Salvo ; Bömmels, Peter ; Dahn, Walter ; Disler, Martin ; etc.
Duits
boek